Interval Enclosures for Reliability Metrics - Campos, Marcilia Andrade; Mendonça, André Feitoza (Trends in Computational and Applied Mathematics, 2016)
The computation of reliability metrics involves real numbers. Therefore, numerical problems are generated due to the limitation of representing and operating with real numbers in computers. This paper proposes interval functions for controlling numeric errors in the computation of reliability metrics values of complex systems, based on interval mathematics and high accuracy arithmetic. The interval functions calculate interval enclosures, using Intlab toolbox, for real values of reliability metrics and the SHARPE software was used to validate the results. Analysis of the numerical results obtained with the proposed functions showed that the intervals really enclose the real numbers calculated by the software SHARPE, indicating that these functions, in fact, are an alternative for auto-validating representation of these reliability values of complex systems.